2021
DOI: 10.21203/rs.3.rs-616496/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A New Hendra Virus Genotype Found in Australian Flying Foxes

Abstract: Background Hendra virus (HeV) has caused lethal disease outbreaks in humans and horses in Australia. Pteropid bats (flying foxes) are the wildlife reservoir from which the virus was first isolated in 1996. Following a heat stress mortality event in Australian flying foxes in 2013, a novel HeV variant was discovered. This study describes the subsequent surveillance of Australian flying foxes for this novel virus over a nine year period using qRT-PCR testing of bat tissues submitted primarily for Australian bat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…In Australia, bat species of the genus Pteropus are reservoir hosts for Hendra virus and Menangle virus, zoonotic pathogens of the family Paramyxoviridae (Halpin et al, 2000, Philbey et al, 1998), as well as Australian bat lyssavirus, a zoonotic virus of the Rhabdoviridae that causes rabies in mammals (Gould et al, 1998). Studies of viruses in bats in Australia have largely focused on these virus families and recently identified a new member of the Paramyxoviridae – Cedar virus – as well as a novel genotype of Hendra virus (Wang et al, 2021, Marsh et al, 2012). Although important, these studies lack information on overall virome composition, particularly those virus families not included in targeted PCR studies.…”
Section: Introductionmentioning
confidence: 99%
“…In Australia, bat species of the genus Pteropus are reservoir hosts for Hendra virus and Menangle virus, zoonotic pathogens of the family Paramyxoviridae (Halpin et al, 2000, Philbey et al, 1998), as well as Australian bat lyssavirus, a zoonotic virus of the Rhabdoviridae that causes rabies in mammals (Gould et al, 1998). Studies of viruses in bats in Australia have largely focused on these virus families and recently identified a new member of the Paramyxoviridae – Cedar virus – as well as a novel genotype of Hendra virus (Wang et al, 2021, Marsh et al, 2012). Although important, these studies lack information on overall virome composition, particularly those virus families not included in targeted PCR studies.…”
Section: Introductionmentioning
confidence: 99%
“…Roosts are spatially discrete, separated by an average distance of 6.9 km (interquartile range 1.6–9.4 km; Figure 1; National Flying‐Fox Monitoring Program, 2017). P. alecto are believed to be the primary reservoir for Hendra virus in this study region (Goldspink et al., 2015); however, a newly identified Hendra virus variant has been detected in P. poliocephalus and P. scapulatus tissues (Wang et al., 2021). All sites were previously documented as having continuous occupation by at least one species of flying‐fox (National Flying‐Fox Monitoring Program, 2017).…”
Section: Methodsmentioning
confidence: 94%
“…Studies focused on herpesviruses have notably revealed that cell-cell fusion phenotype can significantly differ across isolates of the same viral species [166]. As sequences of henipaviruses detected in domestic and wild species are becoming available [167][168][169], it is important to consider a diversity of henipavirus isolates in comparative studies to understand how cell-cell fusion phenotype varies across viruses and how it correlates with spillover risk.…”
Section: Knowns and Unknowns Of Syncytium Formation And Future Directionsmentioning
confidence: 99%